Exploring the Determinants of Turnover Intention Among Elderly-Care Workers - Shen, Zhongping; Apibunyopas, Jeerakiat; Swatdikun, Trairong (Science, Technology, and Social Sciences Procedia, 2023)
In the context of China’s rapid aging society, this study aims to provide practical countermeasures and suggestions to nursing institutions for reducing turnover intention among these workers. Convenient sampling was employed, encompassing all elderly-care workers from 4 nursing institutions in Zhejiang Province as participants. Questionnaires were designed using scales to measure needs satisfaction and turnover intention. A total of 222 valid questionnaires were collected, yielding an effective recovery rate of 97.37 %. Among the participants, 88 individuals (39.64 %) exhibited high turnover intention. Results indicated that social needs satisfaction was the highest, with 94.6 % of participants reporting satisfaction, while physiological needs satisfaction was the lowest, with only 70.7 % expressing higher satisfaction. Univariate analysis demonstrated that younger age, higher education background, fewer children, and increased days of rest per month were associated with higher turnover intention. Furthermore, lower needs satisfaction across all levels correlated with higher turnover intention. Logistic regression analysis revealed that individuals with lower satisfaction in respect needs had a higher turnover intention (OR = 11.265, p < 0.01). Compared to the youngest age group (40 years), older age was associated with lower turnover intention, with an odds ratio of 0.458 (P = 0.171) for the 41 - 50 age group and 0.202 (P = 0.002) for those above 51 years old. Based on these findings, pension agency managers should prioritize addressing physiological needs, respect needs, and self-realization needs, while considering specific items associated with low satisfaction levels. This can be achieved through the implementation of management systems, assessments, and work mechanisms to better meet the needs of elderly-care workers and reduce their turnover intention.